Handbook of research on developing circular, digital, and green economies in Asia - Ordóñez de Pablos, Patricia, 1975- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book explores new and emerging business and management practices to support companies and economies in the digital transformation in Asia, with special emphasis on success and failure experiences and analyzing the role of digital skills and competences, green issues and technological disruptors in these emerging practices in Asia and how they can contribute to the creation of new business opportunities, more jobs and growth for the recovery of Asian economies after the pandemic"--